Elementary Teachers' Self-Efficacy During Initial Implementation of Comprehensive, Integrated, Three-Tiered Models of Prevention. (April 2021) - Oakes, Wendy Peia; Lane, Kathleen Lynne; Royer, David James; Menzies, Holly M.; Buckman, Mark Matthew; Brunsting, Nelson; Cantwell, Emily D.; Schatschneider, Christopher; Lane, Nathan Allen
In this article, we examined educators' efficacy and burnout within Comprehensive, Integrated, Three-tiered (Ci3T) models of prevention, as implemented in 14 elementary schools in a Midwestern state. Participating schools completed a year-long training series to design their Ci3T plans and were in their second year of implementation as part of a districtwide initiative. We examined educators' year-end self-ratings to describe how teachers in schools with prevention models were faring, exploring three sets of variables (a) self-reported Ci3T treatment integrity, (b) social validity ratings of their Ci3T model of prevention, and (c) educators' sense of efficacy and burnout. Results indicated educators experienced emotional exhaustion; however, depersonalization and personal accomplishment scores revealed positive and large magnitude differences compared with a national sample. Moreover, educators reported higher levels of efficacy related to instructional strategies and classroom management than a national sample. Higher self-reported levels of Ci3T treatment integrity were associated with increased levels of efficacy related to student engagement. We discuss limitations and future directions.